2005
DOI: 10.1097/00000542-200504000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Atelectasis

Abstract: Atelectasis occurs in the dependent parts of the lungs of most patients who are anesthetized. Development of atelectasis is associated with decreased lung compliance, impairment of oxygenation, increased pulmonary vascular resistance, and development of lung injury. The adverse effects of atelectasis persist into the postoperative period and can impact patient recovery. This review article focuses on the causes, nature, and diagnosis of atelectasis. The authors discuss the effects and implications of atelectas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
18

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(191 citation statements)
references
References 112 publications
5
168
0
18
Order By: Relevance
“…15 Anesthesia and muscle paralysis have been demonstrated to favor atelectasis formation by reducing functional residual capacity, particularly in markedly obese patients with high intra-abdominal pressure. 15,16,23 It is possible that the high-resistance ETT ensues an increase in auto-PEEP preventing the development of atelectasis. 24 We excluded patients with radiological chest abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…15 Anesthesia and muscle paralysis have been demonstrated to favor atelectasis formation by reducing functional residual capacity, particularly in markedly obese patients with high intra-abdominal pressure. 15,16,23 It is possible that the high-resistance ETT ensues an increase in auto-PEEP preventing the development of atelectasis. 24 We excluded patients with radiological chest abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Atelectasis develops through the compression of lung parenchyma, resorption of alveolar gas, and impaired surfactant function 24. Induction of general anesthesia and chemical paralysis alters the geometry and function of the diaphragm and chest wall, leading to increased pleural pressure and collapse of dependent lung regions 2526.…”
Section: Perioperative Lung Injurymentioning
confidence: 99%
“…In addition, the sigh reflex used to mitigate atelectasis in the awake state is abolished under anesthesia 30. Atelectasis has many adverse physiologic consequences including intrapulmonary shunting, decreased compliance, increased pulmonary vascular resistance, and susceptibility to inflammatory lung injury 9243132. This susceptibility is potentially not limited solely to atelectatic lung segments, as preclinical data have shown that concurrent inflammation can occur remotely in regions with intact ventilation 33.…”
Section: Perioperative Lung Injurymentioning
confidence: 99%
“…Para reexpandir áreas com atelectasia é necessário que os plugs de muco sejam removidos e que ocorra aumento da pressão transpulmonar 36,37,38 . A técnica de compressão e descompressão torácica brusca auxilia na remoção do muco, pois aumenta o tempo expiratório, mas não contribui para a reexpansão pulmonar em pediatria, pois para que isto ocorra é necessária a utilização de altas pressões inspiratórias 36 .…”
Section: Prevenção E Tratamentounclassified